Oxygen-tolerant H2 oxidation by membrane-bound [NiFe] hydrogenases of ralstonia species. Coping with low level H2 in air. - Ludwig, M; Cracknell, J; Vincent, K; Armstrong, F; Lenz, O (2009)
Knallgas bacteria such as certain Ralstonia spp. are able to obtain metabolic energy by oxidizing trace levels of H2 using O2 as the terminal electron acceptor. The [NiFe] hydrogenases produced by these organisms are unusual in their ability to oxidize H2 in the presence of O2, which is a potent inactivator of most hydrogenases through attack at the active site. To probe the origin of this unusual O2 tolerance, we conducted a study on the membrane-bound hydrogenase from Ralstonia eutropha H16 and that of the closely related organism Ralstonia metallidurans CH34, which was purified using a new heterologous overproduction system. Direct electrochemical methods were used to determine apparent inhibition constants for O2 inhibition of H2 oxidation (K I(app)O2) for each enzyme. These values were at least 2 orders of magnitude higher than those of "standard" [NiFe] hydrogenases. Amino acids close to the active site were exchanged in the membrane-bound hydrogenase of R. eutropha H16 for those from standard hydrogenases to probe the role of individual residues in conferring O2 sensitivity. Michaelis constants for H2 (K M H2) were determined, and for some mutants these were increased more than 20-fold relative to the wild type. Mutations resulting in membrane-bound hydrogenase enzymes with increased K M H2 or decreased K I(app)O2 values were associated with impaired lithoautotrophic growth in the presence of high O2 concentrations.